AI-based career profiling for the creative industry: Data-driven classification of islamic high school students' potential - Nove Kurniati Sari; Dias Aziz Pramudita; Syaddam Syaddam; Zainal Abidin Muhja (Journal of Soft Computing Exploration, 2026)
The creative industry is a major contributor to the global economy, especially vital to ASEAN's growth. The sustainability of the sector depends on skilled human resources, which in turn influences cultural and educational policies. Islamic schools are uniquely positioned to develop the character and competence of students. However, Islamic schools in border areas face challenges in accessing resources, particularly in matching students with their interests and talents in the creative field, which is crucial for fulfilling the human resources needs of the creative industry. This research aims to classify students' knowledge and abilities in the creative field so that student competency mapping can be carried out. Using AI modelling tools, naïve bayes can perform classifications with a value of 100% accuracy. In this study, there were 17 data samples of Islamic school students based on their characteristics, learning styles, and creativity levels. Seven students were identified as Creative Innovator Profiles, work-ready, and 10 students as Creative Innovator Profiles, further education-bound. With the existence of a student data classification developer model, it is hoped that the school can switch from general career guidance to personalized guidance supported by data. This marks a significant step towards implementing smart school governance.